Penguatan Kegiatan Media Digital Kantor Urusan Haji Konsulat Jenderal Republik Indonesia Jeddah - Ausath, Wafi R.A.; Rabbani, Ahmad F.; Adyanto, Avicenna M.; Luthfi, Muhammad K.; Azra, Ghailan M.; Widodo , Aris S. (Universitas Muhammadiyah Yogyakarta, 2025)
is a form of community service activity by students with a cross-disciplinary and sectoral approach at a certain time and region. The PKMactivity in the international scheme organized by the Muhammadiyah University of Yogyakarta in Saudi Arabia Batch 5, precisely at the Technical Office of Hajj Affairs of the Indonesian Consulate General in Jeddah, focuses on